Man within machines: Snowpiercer from bande dessinée to film. Issue 2 (2nd April 2016) - Dima, Vlad
Abstract : As a bande dessinée (BD; 1984) and a film adaptation (2013), Le Trainsperceneige / Snowpiercer complicates the phenomenological definition of Being by blurring the lines between man and machine – man is mechanised and the machine is humanised – to such an extent that they essentially coalesce. This essay explores the complicated relationship between the two, supposedly independent, entities at three levels of machinery: man within the philosophical machine of Being, man within the machine of capitalism, and, finally, man within the apparatus machine of the BD and of the film.